Morphology and distribution of sensilla on the antennae and mouthparts of adult Monochamus saltuarius Gebler (Coleoptera: Cerambycidae) - Wang, Jianjun; Wang, Jianguo; Wang, Jingxian; Jiang, Xu; Ren, Shitan; Cao, Chuanwang (Frontiers in Insect Science, 2025)
Monochamus saltuarius is an important wood-boring pest of forests and a vector insect for the transmission of Bursaphelenchus xylophilus in China and other East Asian regions. To gain insight into the Mo. saltuarius olfactory system, we characterized the sizes and morphological characteristics of sensilla on antennae, maxillary palps, and labial palps of adults by scanning electron microscopy. Eight types of antennal sensilla were identified on the antennae: Böhm bristles (BBs), sensilla chaetica (SChs, with subtypes SChI and SChII), sensilla trichodea (STs, with subtypes STI, STII and STIII), sensilla auricillica (SAus), sensilla basiconica (SBs, with subtypes SBI and SBII), sensilla grooved peg (SGPs), dome shaped organs (DSOs), and cuticular pores (CPs); among these, BBs, STIs, STIIs, SChIs, and SChIIs may be mechanoreceptors, and STIIIs, SAus, SBIs, SBIIs, SGPs and CPs may be chemoreceptors. Seven sensillum types were identified on maxillary palps and labial palps: BBs, STs (with subtypes STII, and STIII), SChs, sensilla placodea (SPs), sensilla coeloconica (SCos), CPs, and sensilla twig basiconica (STBs, with subtypes STBI, STBII, STBIII, and STBIV), among which BBs, STIIs, and SChs may be mechanoreceptors, and STIIIs, SPs, CPs, STBIs, STBIIs, STBIIIs, and STIVs may be chemoreceptors. DSOs on the antennae and SCos on the palps may be hydroreceptors, and/or thermoreceptors. The types and densities of sensilla increased from the base to the tip of the antennae, and sensilla with chemical-sensing functions were concentrated mostly on the flagellum. Identification of these sensillum types provides a basis for analyzing the mechanisms of host recognition and environmental perception of Mo. saltuarius.